"EDUCATIONAL, SOCIAL, AND COMMUNICATIVE APPROACHES IN TEACHING PRONUNCIATION TO CHILDREN WITH HEARING IMPAIRMENTS." - Somatova Munavvarxon. Sultonova Munira (Western European Studies, 2024)
This article provides an understanding of hearing-impaired children, the most effective methods of teaching and training them, some elementary problems encountered in teaching deaf children to speak, and pedagogical recommendations for providing them with social and communicative support in the process of education.
Keywords: Hearing impaired children; Pronunciation problems; social adaptation